Does physical activity influence health behavior, mental health, and psychological resilience under the moderating role of quality of life? - Liu, Ru; Menhas, Rashid; Saqib, Zulkaif Ahmed (Frontiers in Psychology, 2024)
Background: Physical activity significantly influences health-related behaviors, encompassing physical and mental well-being. Physical activity has been linked to enhancing health behavior, mental health, and psychological resilience. The current study is based on participants who were active in physical activity to improve health and well-being. Objectives: To examine the influences of physical activity on health behavior, mental health, and psychological resilience, considering the moderating role of quality of life. Method: A thorough cross-sectional online survey was conducted from April 15, 2023, to October 15, 2023. The survey was comprehensive and lasted for six months. The online poll received more than one thousand responses under convenience sampling. The selection criteria for the study were above 21 years old, and participants were active in physical activity to improve health and well-being. The collected data were analyzed using appropriate statistical SPSS-25 and SmartPLS 4.0 software to investigate the proposed research paradigm. Results: SEM results of model 1 (direct coefficients) show that PA has a positive effect on HeB, MeH, PsR, HeB on MeH, HeB on PsR. Out of six (in model 2, four moderating effects of QOL were significant, and two were statistically insignificant. Conclusion: It has been observed that the quality of life has a moderating role in the relationships between physical exercise and several aspects, such as psychological resilience, mental health, and health-related behavior. It is imperative to emphasize the importance of fostering consistent engagement in physical activity to cultivate a well-balanced and health-conscious way of life.